1991
DOI: 10.1143/jjap.30.l1907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultraviolet Light Irradiation on Noncontact Laser Microwave Lifetime Measurement

Abstract: An ultraviolet (UV) irradiation effect on minority-carrier recombination lifetime measured by a noncontact laser/microwave (LM) method is investigated for silicon wafers with native oxide. After UV irradiation, the surface recombination velocity greatly decreased resulting in the increase in the effective recombination lifetime (τeff). The effect disappears rapidly with time after the irradiation, and τeff recovers to the initial value after several minutes at room temperature. Since the UV irradiation process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…UV illumination of crystalline silicon has been reported to decrease the surface recombination velocity for p-type crystalline silicon samples with a native oxide layer [22,23]. This effect, however, which has been explained by charging and discharging of slow states in the native oxide, was not stable in time, in contrast to the results reported in the present study.…”
Section: Resultscontrasting
confidence: 99%
“…UV illumination of crystalline silicon has been reported to decrease the surface recombination velocity for p-type crystalline silicon samples with a native oxide layer [22,23]. This effect, however, which has been explained by charging and discharging of slow states in the native oxide, was not stable in time, in contrast to the results reported in the present study.…”
Section: Resultscontrasting
confidence: 99%
“…The measurement techniques for charge trapping and de-trapping include the capacitance-voltage (C-V) measurement [3][4][5][6][7], laser-microwave photoconductance decay (LM-PCD) measurement [8][9][10] and electron spin resonance (ESR) measurement [11][12][13][14][15]. Zhong and Shimura [16] reported that the UV irradiation (4.9 eV) on oxidized silicon wafers dramatically decreased the effective minority carrier recombination lifetime, which was attributed to the generation of interface traps.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The minority carrier recombination lifetime measured by the -PCD technique is also commonly recognized as a useful index for the evaluation of crystallographic imperfections which could act as trap centers. 5 In the silicon wafer industry, the mechanical damage method, which provides dislocation and/or stacking fault nuclei 6,7 on wafer back side, is one of the extensively used extrinsic gettering techniques 8 costly. In this study, a systematic experimental investigation into the effect of mechanical back side damage on structural and electrical properties of silicon wafers was evaluated using high resolution x-rays, x-ray topography, and minority carrier recombination lifetime measurements.…”
Section: Introductionmentioning
confidence: 99%